ANALISIS LOYALITAS NASABAH BANK BCA YANG DITINJAU DARI KUALITAS LAYANAN, CITRA BANK, DAN KEPERCAYAAN - Tanto Askriyandoko Putro; Irene Maharani (Ma Chung Press, 2026)
This study aims to examine and analyze the influence of service quality, bank image, and trust on customer loyalty at Bank Central Asia (BCA) Blitar Branch. The research method used was a quantitative approach with systematic data analysis. The results showed that all three independent variables significantly influenced customer loyalty. Service quality was shown to have a positive effect, meaning that the better the service provided, the higher the customer loyalty. Bank image also had a significant impact, where positive public perception of the bank's reputation increased customer loyalty. Furthermore, customer trust in BCA plays a crucial role in strengthening long-term relationships between customers and the bank. Overall, these findings confirm that service quality, bank image, and trust are key factors that complement each other in building and enhancing customer loyalty at BCA Blitar Branch.